The Implementation Mechanism, Application, And Development Prospects Of Turkey’s Drone Strategy - Kuang-Ho Yeh (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Drones possess precise intelligence gathering, casualty avoidance, and remote strikes as an emerging strategic technology. With the rapid development of functionality and application modes, drones have become a new focal point in international military competition. In recent years, the operational contributions of Turkish drones in multiple battles have attracted global attention. This article examines the background formation, implementation mechanisms, and further prospects of Turkey’s drone strategy to understand the complex factors behind the particular development patterns. This article adopts the analytic hierarchy process and draws on current literature and case studies, analyzing multiple perspectives of Turkey’s drone strategy from two hierarchical levels: domestic politics and international environments. As a latecomer, Turkey has made significant strategic achievements in the field of drones. The analysis of Turkey’s strategic planning and practices in domestic and international arenas in different periods hold a certain degree of reference for drone development both in China and in the international society.
Keywords: International relations